Virtual Reality Media for Fun Learning - Refmidawati (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Organizations can support and enhance knowledge management methods with the use of technologies. To begin with, it will be simpler to define the terms augmented and virtual reality to comprehend them better. Knowledge management processes can be enhanced and supported by enterprises through the use of artificial intelligence technologies. The study aims to elucidate the present trend in science education involving artificial intelligence and augmented reality. A review of the most recent techniques is carried out by following the recommended reporting items for reviews and meta-analyses (PRISMA) criteria. The development of AI technology is one innovation in educational technology to aid in learning. If technology is used sensibly and appropriately, it can expedite education. The advancement of artificial intelligence technology has the potential to foster greater independence in students. Although the teacher does not need to take on such a prominent role, his duties are outlined in providing clarity through important keywords. Managing student conduct and morale is the cornerstone of education, and it should be the foundation for all technology use by educators.